An intercountry comparison of the impact of the paediatric live attenuated influenza vaccine (LAIV) programme across the UK and the Republic of Ireland (ROI), 2010 to 2017. Issue 2 (13th February 2023) - Sinnathamby, Mary A.; Warburton, Fiona; Reynolds, Arlene J.; Cottrell, Simon; O'Doherty, Mark; Domegan, Lisa; O'Donnell, Joan; Johnston, Jillian; Yonova, Ivelina; Elgohari, Suzanne; Boddington, Nicola L.; Andrews, Nick; et al.
Abstract: Background: The universal paediatric live attenuated influenza vaccine (LAIV) programme commenced in the United Kingdom (UK) in 2013/2014. Since 2014/2015, all pre‐school and primary school children in Scotland and Northern Ireland have been offered the vaccine. England and Wales incrementally introduced the programme with additional school age cohorts being vaccinated each season. The Republic of Ireland (ROI) had no universal paediatric programme before 2017. We evaluated the potential population impact of vaccinating primary school‐aged children across the five countries up to the 2016/2017 influenza season. Methods: We compared rates of primary care influenza‐like illness (ILI) consultations, confirmed influenza intensive care unit (ICU) admissions, and all‐cause excess mortality using standardised methods. To further quantify the impact, a scoring system was developed where each weekly rate/z‐score was scored and summed across each influenza season according to the weekly respective threshold experienced in each country. Results: Results highlight ILI consultation rates in the four seasons' post‐programme, breached baseline thresholds once or not at all in Scotland and Northern Ireland; in three out of the four seasons in England and Wales; and in all four seasons in ROI. No differences were observed in the seasons' post‐programme introduction between countries in rates of ICU and excess mortality, although reductions in influenza‐related mortality were seen. The scoring system also reflected similar results overall. Conclusions: Findings of this study suggest that LAIV vaccination of primary school age children is associated with population‐level benefits, particularly in reducing infection incidence in primary care.